Cardiovascular risk in women with polycystic ovarian syndrome (PCOS). Issue 2 (27th January 2005) - Bickerton, A S T; Clark, N; Meeking, D; Shaw, K M; Crook, M; Lumb, P; Turner, C; Cummings, M H
Abstract : Aims: Studies have suggested that polycystic ovary syndrome (PCOS) is associated with increased cardiovascular risk. The aim of this study was to examine cardiovascular risk profiles in women with PCOS compared with healthy age and weight matched control subjects using novel biochemical and biophysical markers. Methods: After ethics committee approval, 11 women with PCOS and 12 controls were recruited (mean age, 32; SD, 6.5 years; mean body mass index (BMI), 33.1; SD, 5.9 kg/m 2 ). Serum was analysed for lipid and lipoprotein profile (total and high density lipoprotein cholesterol, triglycerides, apolipoprotein B-100, apolipoprotein A1, lipoprotein (a)), and sialic acid, fibrinogen, homocysteine, and C reactive protein (CRP) concentrations. Endothelial function was also assessed by a standard venous occlusion plethysmography technique to measure reactive hyperaemic forearm blood flow (RH), and expressed as per cent increase from baseline. Results: There were no significant differences in glucose, lipid, or lipoprotein concentrations between the two groups. Furthermore, sialic acid (PCOS: mean, 70.5; SD, 149 mg/litre; controls: mean, 71.3; SD, 112 mg/litre), fibrinogen (PCOS: mean, 3.1; SD, 1.0 g/litre; controls: mean, 3.3; SD, 0.7 g/litre), CRP (PCOS: mean, 4.6; SD, 4.2 mg/litre; controls: mean, 5.4l SD, 5.5 mg/litre), and RH (PCOS: mean, 158.7; SD, 135.5%; controls: mean, 200.1; SD, 114.2%) were similar. Conclusions: There were no differences in surrogate markers of the processes linked to enhanced cardiovascular risk between patients with PCOS and weight matched controls.